Studies on bacterial flora of Murrah buffalo semen and their antibiogram - SINGH, M P; SAXENA, M S; LAKHCHAURA, B D; PRASAD, J K (The Indian Journal of Animal Reproduction, 2023)
A total of37 bacterial isolates were obtained from 28 neat semen samples of Murrah buffalo bulls. Out of37 isolated bacteria 15, 20 18 were gram positive and 19 were gram negative. The isolated bacteria included Bacillus s 29, 20p., staphylococcusaureus, Staphylococcus epidermidis, Streptococcus sp., Alcaligenes faecalis, Serratia sp., Salmonella sp., Pseudomonas aeruginosa, Shigella sp. and Klebsiella sp. Antibiotic sensitivity test was performed against I 2 different antibiotic discs (Amikacin, enrotloxacin, gentamicin, chloramphenicol, ciprotloxacin, nortloxacin cephalexin, streptomycin, amoxycillin, ampicillin, erythromycin and penicillin). The results of sensitivity test revealed that gram positive bacteria were more susceptible as compared to gram negative bacteria with antimicrobials used in the study. Bacillus sp. was found to be susceptible to all the antimicrobials used, whereas Pseuodomonas aeruginosa was sensitive to Amikacin and Enrotloxacin only. Amikacin was found to be most effective (I 00.00%) against the isolates followed by enrofloxacin (97.30%), genatamicin (97.30%), chloramphenicol (97.30%), ciprotloxacin (97.30%), nortloxacin (94.60%), cephalexin (91.90%) ampicillin (75.70%), penicillin (67.20%), erythromycin (62.20%). amoxycillin (59.50%) and streptomycin (56.80%).